The mindful librarian connecting the practice of mindfulness to librarianship - Moniz, Richard; Eshleman, Joe; Henry, Jo; Slutzky, Howard; Moniz, Lisa (Waltham, MA Chandos Pub (Oxford) Ltd, 2016)
The Mindful Librarian: Connecting the Practice of Mindfulness to Librarianship explores mindfulness, approaching it in such a way as to relate specifically to the many roles or challenges librarians face. Coinciding with the increased need to juggle a variety of tasks, technologies, ebooks, and databases, the new Association of College & Research Libraries Framework for Information Literacy, and the challenges faced by solo librarians in school libraries which have suffered cutbacks in help in recent years, the time is exactly right for this publication. The authors hope to be helpful in some small way towards improving the joy and quality of life that librarians and library science students experience in their personal lives and jobs. The loftier goal would be to create a new lens from which to view librarianship, having a transformative impact on readers, and opening a new dialog within the profession. The topic of mindfulness is not new; it has been connected to various religious traditions in a wide variety of ways for centuries, most notably Buddhism. In the latter part of the 20th century, however, a secular version was popularized largely by the work of Jon Kabat-Zinn and his work on MBSR (Mindfulness Based Stress Reduction) at the University of Massachusetts's Medical School. The medical benefits and the overall quality of life improvements from its adoption have exploded in recent years, in particular, the last two decades which have seen mindfulness traditions incorporated into education to a greater degree and with very positive results.
Includes bibliographical references and index.
Keywords: Librarians; Mindfulness (Psychology)